Effect of legowo planting system and doses of cow manure on growth and yield of maize (Zea mays L.) - Munandar Labongkeng; Lani Pelia; Hertasning Yatim (Faculty of Agriculture, Tompotika Luwuk University, 2021)
Increasing of maize productivity can be reched through using of superior varieties BISI 18, aplication of organic fertilizer, and regulation of crop populations. This study was aimed to know the influence of jajar legowo planting system (2:1) and cow manure on growth and yield of maize. This research was conducted in Bualemo B, Bualemo, Banggai from July up to October 2020. The experiment was arranged in Randomized Block Design with 2 factors, the first factor is the spacing of planting in legowo planting system (2:1), which consists of 3 levels namely 70 x 25 x 25 cm (J1), 70 x 30 x 30 cm (J2), 70 x 35 x 35 cm (J3), the second factor is the dose of manure which consists of 3 levels namely 8 tons/ha (K1), 9 tons/ha (K2), and 10 tons/ha (K3). Each treatment had 3 replications so there were 27 treatment plots. The results showed that the combination of jajar legowo planting system and cow manure has no effect on the height of plants at 2, 4, and 6 weeks after planting, as well as the number of leaves, but giving the effect on the height of plants at 8 weeks after planting. The combination of jajar legowo planting system and cow manure has a real effect on the average weight of cob and has a very real effect on dry weight per plot. The weight average in corn cobs about 239.67 grams in the spacing of planting 70 x 35 x 35 cm with 8 tons/ha dose of manure. While the grain dry weight average is highest in the spacing of planting 70 x 35 x 35 cm with 10 tons/ha dose of manure and it is about 212.56 ounces.